Development and research of nanostructured multilayer composite coatings for tungsten-free carbides with extended area of technological applications. Issue 9 (December 2016) - Vereschaka, A.; Vereschaka, A.; Batako, A.; Hojaev, O.; Mokritskii, B.
Abstract This paper discusses aspects of the development of nanostructured multilayer composite coatings (NMCCs) formed using the processes of filtered cathodic vacuum arc deposition (FCVAD) for application to the tungsten-free carbides (cermets) based on TiC-(Ni, Mo) and TiCN-(Ni, Mo) compounds in order to improve cutting properties of tools and to expand the area of their technological application. NMCCs were used not only to improve the physical and mechanical properties of the working surfaces of tools but also to ensure the control over contact processes during cutting. The study has shown that despite their high hardness, thermal stability and resistance to scaling, low tendency to diffusion with the material being machined, and tungsten-free carbides are characterized by relatively low fracture toughness and bending strength, low thermal conductivity. With regard to the above properties, tungsten-free carbides are inferior not only to tungsten WC-Co carbides but also to WC-TiC-Co carbides with binder content of less than 8 % (by weight). Therefore, cutting tools made of tungsten-free carbides have a limited range of technological application in interrupted cutting, machining of hard-to-cut alloys and steels. With respect to this, the paper considers the possibility of directional control over contact processes during cutting with the use of NMCCs to create more balanced properties of tungsten-free carbides with regard to hardness and toughness. This work has developed architecture of three-component nanostructured multilayer composite coatings, the methods for selecting functions and rational component parameters of architecture for tools made of tungsten-free carbides. The developed compositions of NMCCs have improved cutting properties of tungsten-free carbides and expanded the area of their technological application in cutting of heat-treated steels of increased hardness and machining of heat-resistant alloys.